Investigating Determinants of Intention in Cash Waqf Linked Sukuk for Sustainable Agriculture: The Moderating Role of Environmental Awareness - Salam, Annisa Nur; Sutisna, Fajar Andrian (Universitas Islam Internasional Indonesia, 2024)
The role of cash waqf linked sukuk (Islamic bonds linked to endowments) should be developed to enhance the green economy, particularly in the sustainable agriculture sector. This study investigates the influence of Islamic religiosity, knowledge, and trust in nazhir (waqf managers) on the intention to engage in cash waqf linked sukuk transactions for sustainable agriculture. This study also analyzes the moderating role of environmental awareness as an important factor in the green economy. Primary data was collected through questionnaires disseminated to 150 respondents and Partial Least Squares Structural Equation Modeling (PLS SEM) was employed to analyze the data. The findings indicate that environmental awareness and trust nazhir are significant determinants of the intention to engage in cash waqf linked sukuk transactions for sustainable agriculture. Environmental awareness is also found to be significant in moderating the influence of Islamic religiosity. The implications suggest that to enhance community participation in cash waqf linked sukuk for sustainable agriculture, it is imperative to build trust in nazhir, increase environmental awareness, and target individuals who uphold Islamic values.